Radiochemotherapy for locally advanced squamous cell carcinoma of the head and neck: Higher-dose cisplatin every 3 weeks versus cisplatin/5-fluorouracil every 4 weeks. Issue 9 (September 2016) - Rades, Dirk; Strojan, Primoz; Seidl, Daniel; Janssen, Stefan; Bajrovic, Amira; Kazic, Nadja; Hakim, Samer G.; Wollenberg, Barbara; Schild, Steven E.
Abstract: Many patients with locally advanced squamous cell carcinoma of the head and neck (LASCCHN) receive cisplatin-based radiochemotherapy. The optimal regimen is still unclear when considering both efficacy and feasibility. This study compared two regimens for locoregional control (LRC), overall survival (OS), and adverse events. Data of 329 patients with LASCCHN receiving definitive or postoperative radiochemotherapy were retrospectively analyzed. A total of 131 patients received 100 mg/m 2 cisplatin on days 1, 22, and 43 (group A), and 198 patients received 20 mg/m 2 cisplatin plus 600/1000 mg/m 2 5-FU on days 1–5 and days 29–33 (group B). Radiochemotherapy regimens plus nine factors were compared for LRC and OS, and radiochemotherapy regimens additionally for adverse events. On univariate analysis, chemotherapy type was not associated with LRC (p = 0.36). On multivariate analysis, performance score (p = 0.039), N-category (p = 0.007), histologic grade (p = 0.007), upfront surgery (p = 0.030), and pre-radiochemotherapy hemoglobin levels (p < 0.001) were associated with LRC. On univariate analysis, chemotherapy type had no impact on OS (p = 0.64). On multivariate analysis, performance score (p < 0.001), T-category (p = 0.025), N-category (p < 0.001), histologic grade, and hemoglobin levels (p < 0.001) were associated with OS. Renal failure occurred significantly more often in group A (p = 0.008). Otherwise, adverse events were not significantly different. Thus, both radiochemotherapy regimens appeared similarly effective for LASCCHN. Patients receiving 100 mg/m 2 of cisplatin require close monitoring of their renal function.